Thermal stability of melt-blended poly (lactic acid) (PLA)/polyamide 66 (PA66)/graphene nanoplatelets (GnP) - Alhadadi, W.; Almaqtari, A.; Hafidzah, F.; Mohd Bijarimi, Mat Piah; Desa, M. S. Z.; Merzah, H.; Normaya, E.; Norazmi, M. (IOP Publishing, 2020)
In recent times the blending of different biodegradable materials to produce nanocomposites with improved properties has been a significant point of discourse by many researchers. This study reports a melt blend of poly (lactic acid) (PLA), polyamide (Nylon 66) and graphene nanoplatelets (GnP). The thermal stability and chemical functional characteristics of the nanocomposites produced were succinctly investigated using thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and Fourier transform infrared (FTIR). The blending was carried out by using a twin-screw extruder at a revolution speed and time of 50 rpm and 20 minutes, respectively. The composition of GnP in the PLA/PA66 was varied from 0 – 5 wt.%. The results showed that the increased of the GnP concentrations improved the thermal stability of the nanocomposites. It was also observed that a strong interaction between the polymeric materials as demonstrated by the FTIR analysis. The use of a low concentration of graphene in PLA/PA66 blend has been demonstrated to improve the thermal stability of the nanocomposites.